O amazônida Samuel Soares de Almeida (1958-2011) - Vieira, Ima Célia Guimarães; Galatti, Ulisses; Amara, Dário (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2011)
Texto em PDF
Keywords: Memória